2003
DOI: 10.1046/j.1365-2494.2003.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyethylene colour and thickness on grass silage quality

Abstract: The aim of the investigation was to determine the influence of variations in thickness and colour of agricultural plastic film on silage preservation conditions and grass silage quality. For this purpose, 30 cylindrical plastic containers (mini‐silos; 0·3 m3) were filled with chopped grass and covered with five films of different thickness and colour: 90 μm, white; 125 μm, green; 150 μm, black; 200 μm, green and 200 μm, white. Four replications of each film type were placed in the open air. Two replications we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…When investigating PE films of different thicknesses (100, 150 and 200 μm), Savoie (1988) did not report significant differences in losses after 130 d of storage (on average 2 g kg −1 month −1 ). Similar results have been observed by Snell et al. (2002, 2003) who reported that the thickness of the PE films does not have any significant influence on the chemical analysis of silage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When investigating PE films of different thicknesses (100, 150 and 200 μm), Savoie (1988) did not report significant differences in losses after 130 d of storage (on average 2 g kg −1 month −1 ). Similar results have been observed by Snell et al. (2002, 2003) who reported that the thickness of the PE films does not have any significant influence on the chemical analysis of silage.…”
Section: Discussionsupporting
confidence: 90%
“…(2002, 2003) who reported that the thickness of the PE films does not have any significant influence on the chemical analysis of silage. For a film to receive a certificate of approval in Germany, the Agricultural Society requires a gas permeability of <250 cm 3 m −2 per 24 hour (Snell et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of stable anaerobic conditions for silage making is unquestioned and low‐density polyethylene (LD‐PE) films are usually used as a barrier against air infiltration, few scientific studies exist on the correlation between the permeability of a film to oxygen and silage quality . Throughout the world, maize ( Zea mays L.) silage is commonly stored in bunker silos and covered with PE film.…”
Section: Introductionmentioning
confidence: 99%
“…In deteriorated samples, this value decreased to 2.2 and 2.9, respectively. Snell et al (2003) found a relation between applications and color values of L* and a*. Ball et al (2017) also emphasized that a bright green color can be an indicator of storage conditions which shows good protection during storage.…”
Section: Resultsmentioning
confidence: 98%